If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7)(4 + 2x) = 56 (4 * 7 + 2x * 7) = 56 (28 + 14x) = 56 Solving 28 + 14x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 14x = 56 + -28 Combine like terms: 28 + -28 = 0 0 + 14x = 56 + -28 14x = 56 + -28 Combine like terms: 56 + -28 = 28 14x = 28 Divide each side by '14'. x = 2 Simplifying x = 2
| 64m^8-49n^6=0 | | -(9x-8)= | | -6x-5x=-11 | | -8=3x+4 | | 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) | | 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 | | -3+14= | | 4d-6=2(3d-4) | | x^2-14x+196=0 | | -25+25= | | 78=-5x+19 | | 18=-5x+19 | | 33=-5x+19 | | 27=-5x+19 | | 2c+6=0.5(4c+12) | | 6a+5b-2a+-b+7a+3c+a= |